2019
DOI: 10.1186/s12936-019-2843-6
|View full text |Cite
|
Sign up to set email alerts
|

The first introduced malaria case reported from Sri Lanka after elimination: implications for preventing the re-introduction of malaria in recently eliminated countries

Abstract: Background There has been no local transmission of malaria in Sri Lanka for 6 years following elimination of the disease in 2012. Malaria vectors are prevalent in parts of the country, and imported malaria cases continue to be reported. The country is therefore at risk of malaria being re-established. The first case of introduced vivax malaria in the country is reported here, and the surveillance and response system that contained the further spread of this infection is described. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…2 Department of Geography, Faculty of Arts, University of Jaffna, Jaffna, Sri Lanka. 3 ID-FISH Technology, Milpitas, CA, USA.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Department of Geography, Faculty of Arts, University of Jaffna, Jaffna, Sri Lanka. 3 ID-FISH Technology, Milpitas, CA, USA.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…However, the approximately 100 travelers with malaria who arrive every year from endemic countries, and the prevalence of potent anopheline vectors throughout the island, pose the risk of reinitiating local malaria transmission [2]. Indeed, an instance of local malaria transmission from a malaria-infected Indian national to a Sri Lankan resident was documented in late 2018 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Resurgence of malaria is often associated with imported infections and/or P. vivax relapsing infections in areas that remain highly receptive to malaria [13][14][15][16]. Studies have demonstrated the usefulness of spatially referenced entomological data to characterise the heterogeneity of malaria receptivity in areas approaching elimination to prevent outbreaks in the future [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Following the elimination of malaria in 2012 and being free from indigenous transmission for six consecutive years, Sri Lanka reported the first case of introduced malaria in December 2018 [3], the source of the infection (index case) being one of a group of foreign workers from India who developed a Plasmodium vivax infection a few days after arriving in Sri Lanka. The location of transmission to the introduced case was a factory construction site in the District of Monaragala, a highly receptive remote area in southwestern Sri Lanka which was previously endemic for malaria; here a group of 32 workers of Indian origin including the index case were employed and resident.…”
Section: Introductionmentioning
confidence: 99%
“…The location of transmission to the introduced case was a factory construction site in the District of Monaragala, a highly receptive remote area in southwestern Sri Lanka which was previously endemic for malaria; here a group of 32 workers of Indian origin including the index case were employed and resident. The area was found to have a high prevalence of Anopheles culicifacies, the primary vector of malaria in the country [3].…”
Section: Introductionmentioning
confidence: 99%